2019
DOI: 10.1080/15283488.2019.1566067
|View full text |Cite
|
Sign up to set email alerts
|

Being Young and Strictly Religious: A Review of the Literature on the Religious Identity Development of Strictly Religious Adolescents

Abstract: Strictly religious adolescents grow up in highly religious contexts with orthodox beliefs and practices that usually contrast with those of pluralist and secularized societies that can be perceived as promoting unhealthy religious identity development. For these adolescents, religious identity development may be a challenge; however, there seems to be a lack of theoretical and empirical understanding of how these adolescents develop their religious identities. To address this, a literature review was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 28 publications
2
11
0
Order By: Relevance
“…With Loveland (2016), we would state that religious identity development "is essentially social" (294). This is in line with other studies (e.g., Cohen-Malayev, Schachter, and Rich 2014;de Bruin-Wassinkmaat et al 2019;Fisherman 2011;Hemming and Madge 2012;Sherkat 2003;Visser-Vogel et al 2015) which showed that religious identity development is shaped and influenced by the context. We use the term "context" in this study of religious identity development to refer to the micro-context of an individual's family, school, church, and peers (Schachter and Ventura 2008).…”
Section: Religious Identity Development and Contextual Influencessupporting
confidence: 93%
See 3 more Smart Citations
“…With Loveland (2016), we would state that religious identity development "is essentially social" (294). This is in line with other studies (e.g., Cohen-Malayev, Schachter, and Rich 2014;de Bruin-Wassinkmaat et al 2019;Fisherman 2011;Hemming and Madge 2012;Sherkat 2003;Visser-Vogel et al 2015) which showed that religious identity development is shaped and influenced by the context. We use the term "context" in this study of religious identity development to refer to the micro-context of an individual's family, school, church, and peers (Schachter and Ventura 2008).…”
Section: Religious Identity Development and Contextual Influencessupporting
confidence: 93%
“…As the term "identity agent" already indicates, contextual influence is often related to agency, which our systematic literature review study confirmed (de Bruin-Wassinkmaat et al 2019). In the scholarship, we observed that there is an ideal image of healthy religious identity development, whereby youth "exercise agency" (Hemming and Madge 2012) and the context honors and stimulates agency.…”
Section: Religious Identity Development and Contextual Influencessupporting
confidence: 75%
See 2 more Smart Citations
“…Although “youth” and “ethnicity” are important identities through which young people develop and transmit their values, religion plays an important role within societal settings of East African youth in Kenya, Rwanda, Tanzania, and Uganda (Awiti and Orwa 2019, 426–27). Religion is an important way in which adolescents can synthesize their other identities into one whole (De Bruin‐Wassinkmaat, De Kock, Visser‐Vogel, Bakker and Barnard 2019, 72). Within the literature, the concept of adolescent identity formation is grounded in Erikson's theory of development which speaks of how young people structure childhood concepts of self and world into a coherent whole (De Bruin‐Wassinkmaat, De Kock, Visser‐Vogel, Bakker, and Barnard 2019, 72), what Erikson (1968, 136) himself refers to as the “counterpointing as well as the fusing of identities.” Elsewhere, Erikson (1968, 83) observes that the rituals involved in religious life bring wholeness to people as they go through the crises of life.…”
Section: Youth Religious and Nonreligious Identity Formationmentioning
confidence: 99%